Curcumin Combined with FOLFOX Chemotherapy Is Safe and Tolerable in Patients with Metastatic Colorectal Cancer in a Randomized Phase IIa Trial. Issue 7 (27th May 2019) - Howells, Lynne M; Iwuji, Chinenye O O; Irving, Glen R B; Barber, Shaun; Walter, Harriet; Sidat, Zahirah; Griffin-Teall, Nicola; Singh, Rajinder; Foreman, Nalini; Patel, Samita R; Morgan, Bruno; Steward, William P; et al.
ABSTRACT: Background: Curcumin is the main active ingredient of the spice turmeric, investigated extensively for putative anticancer properties. Objectives: This phase IIa open-labelled randomized controlled trial aimed to assess safety, efficacy, quality of life, neurotoxicity, curcuminoids, and C-X-C-motif chemokine ligand 1 (CXCL1) in patients receiving folinic acid/5-fluorouracil/oxaliplatin chemotherapy (FOLFOX) compared with FOLFOX + 2 g oral curcumin/d (CUFOX). Methods: Twenty-eight patients aged >18 y with a histological diagnosis of metastatic colorectal cancer were randomly assigned (1:2) to receive either FOLFOX or CUFOX. Safety was assessed by Common Toxicity Criteria-Adverse Event reporting, and efficacy via progression-free survival (PFS) and overall survival (OS). Quality of life and neurotoxicity were assessed using questionnaires (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 and Functional Assessment of Cancer Treatment-Gynecologic Oncology Group-Neurotoxicity). Plasma curcuminoids were determined with liquid chromatography (LC) electrospray ionization tandem mass spectrometry and CXCL1 by ELISA. Results: Addition of daily oral curcumin to FOLFOX chemotherapy was safe and tolerable (primary outcome). Similar adverse event profiles were observed for both arms. In the intention-to-treat population, the HR for PFS was 0.57 (95% CI: 0.24, 1.36; P = 0.2) (median of 171 and 291 d for FOLFOX and CUFOX, respectively) and for OS was 0.34 (95% CI: 0.14, 0.82; P = 0.02) (median of 200 and 502 d for FOLFOX and CUFOX, respectively). There was no significant difference between arms for quality of life ( P = 0.248) or neurotoxicity ( P = 0.223). Curcumin glucuronide was detectable at concentrations >1.00 pmol/mL in 15 of 18 patients receiving CUFOX. Curcumin did not significantly alter CXCL1 over time ( P = 0.712). Conclusion: Curcumin is a safe and tolerable adjunct to FOLFOX chemotherapy in patients with metastatic colorectal cancer. This trial was registered at clinicaltrials.gov as NCT01490996 and at www.clinicaltrialsregister.eu as EudraCT 2011-002289-19.